Polymorphism in 1-Methylhydantoin: Investigation by Periodic DFT Calculations and Characterization of the Third Polymorph - Nogueira, Bernardo A.; Milani, Alberto; ILDIZ, GÜLCE ÖĞRÜÇ; Paixão, José A.; Castiglioni, Chiara; Fausto, Rui (Royal Society of Chemistry, 2020)
In previous studies [Puszyńska-Tuszkanow et al. Polyhedron, 2011, 30(12), 2016; Nogueira et al. J. Phys. Chem. A, 2014, 118(31), 5994; Nogueira et al., J. Mol. Struct., 2017, 1148, 111], two different polymorphs of 1-methylhydantoin (1-MH, C4H6N2O2) were identified (forms I and II) and characterized using infrared and Raman spectroscopies, as well as by X-ray diffraction. In this work, a new polymorph of the compound (form III) is described. The new polymorph was characterized spectroscopically and its structure was determined for the first time by single crystal X-ray diffraction. Very interestingly, the crystal of polymorph III was found to exhibit a high-Z′ (Z′ = 3) asymmetric unit and 12 molecules in the unit cell (Z = 12), which contrasts with the simpler crystal structures found previously for forms I and II (Z = 4; Z′ = 1). Besides, a thorough study of the polymorphism of 1-MH was performed with the help of state-of-the-art first principles fully periodic calculations of the structure, as well as infrared and Raman spectra of the different polymorphs of the compound. Marker-bands in the infrared and Raman spectra of the polymorphs are proposed for fast spectroscopic identification of the polymorphs.
Keywords: Polymorphism